Energy Pricing in the Soviet Union - Kumar, Manmohan (IMF Working Papers; Working Paper ;, 1991)
Energy exports, which are already the primary source of Soviet convertible currency earnings and an important contributor to the budget, could bring in much more revenue if the Soviet Union were to reduce its extremely high levels of energy consumption. To encourage this process, energy prices need to be raised substantially. Under plausible assumptions, it is shown that an increase in prices could yield sizable foreign exchange earnings. Large increases in energy prices could, however, threaten the solvency of industrial enterprises, precipitate major economic and social dislocation, and severely strain interrepublican economic relationships.